Correlates of HIV infection and being unaware of HIV status among soon‐to‐be‐released Ukrainian prisoners. Issue 2 (10th September 2014) - Azbel, Lyuba; Wickersham, Jeffrey A; Grishaev, Yevgeny; Dvoryak, Sergey; Altice, Frederick L
Abstract : Introduction: Prisoners bear a disproportionate burden of Ukraine's volatile and transitional HIV epidemic, yet little is known in Eastern Europe about HIV testing, treatment and HIV‐related risk among prisoners. Methods: A nationally representative biobehavioural health survey linked with serological testing was conducted among soon‐to‐be released prisoners in 13 Ukrainian prisons from June to November 2011. Results: Among 402 participants, 78 (19.4%) tested HIV seropositive of whom 38 (50.7%) were previously unaware of their HIV status. Independent correlates of HIV infection included drug injection (AOR=4.26; 95% CI: 2.23–8.15), female gender (AOR=2.00; 95% CI: 1.06–3.78), previous incarceration (AOR=1.99; 95% CI: 1.07–3.70) and being from Southern Ukraine (AOR=5.46; 95% CI: 2.21–13.46). Those aware of being HIV‐positive reported significantly more pre‐incarceration sex‐ and drug‐related HIV risk behaviours than those who were unaware. Conclusions: Routine rather than risk‐based HIV testing and expansion of opioid substitution and antiretroviral therapy among prisoners is urgently needed to reduce HIV transmission in volatile transitional HIV epidemics.